The Influence of Book-Tax Differences on Earnings Persistence: A Stakeholder Theory Perspective - Agustin Palupi (Jurnal Akuntansi, 2025)
This research investigates the effect of Book-Tax Differences on earnings quality by studying 35 companies within the consumer cyclicals, consumer non-cyclicals, and basic materials sectors. The study includes 105 data points gathered over three years, adhering to six predetermined selection criteria. The companies analyzed were listed on the Indonesia Stock Exchange (IDX) between 2015 and 2022. The findings reveal that permanent book differences (PBD), operating cash flow (OCF), leverage (LEV), and managerial ownership (KM) have no significant influence on earnings quality. In contrast, temporary book differences (TBD) and audit quality (AQ) negatively affect earnings quality, while firm size (SIZE) has a positive impact. Stakeholder theory emphasizes that businesses should account for the interests of all stakeholders, not just shareholders. Analyzing Book-Tax Differences (BTD) is crucial, as it highlights potential inconsistencies between accounting income and taxable income, serving as indicators of financial reporting quality, including earnings persistence.